Trust and communication as predictors of marital intimacy among individuals in dual-earner marriages - Reynalda Fildzah Dessyrianti; Jenny Lukito Setiawan (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
Every year, the labor force grows, owing to an increase in the number of women employed and dual-earner couples, including in Indonesia. Individuals in dual-earner marriages face several problems, such as marital intimacy. This study aimed to investigate the role of trust and communication in marital intimacy among individuals in dual-earner marriages in Surabaya. Participants in this study were 103 individuals in dual-earner marriages in Surabaya, chosen using the convenience sampling technique. This study used three scales: Trust Scale, Communication Scale, and Personal Assessment of Intimacy in Relationship (PAIR) Inventory. Multiple linear regression analysis was used to analyze the data. The results show trust and communication contributed significantly to marital intimacy, with the total effective contribution of the two variables being 74 percent. Trust contributed bigger than that of communication, 68.7 percent and 5.3 percent, respectively. This study concludes that trust and communication simultaneously and partially play a significant role in marital intimacy among individuals in dual-earner marriages in Surabaya. Therefore, to maintain marital intimacy, individuals in dual-earner marriages need to develop trust in their husband or wife.